Lifetime and surface-to-bulk scattering off vacancies of the topological surface state in the three-dimensional strong topological insulators Bi2Te3 and Bi2Se3 - Ruessmann, Philipp; Mavropoulos, Phivos; Blügel, Stefan (JOURNAL OF PHYSICS AND CHEMISTRY OF SOLIDS, 2019)
We analyze the finite lifetimes of the topologically protected electrons in the surface state of Bi2Te3 and Bi2Se3 due to elastic scattering off surface vacancies and as a function of energy. The scattering rates are decomposed into surface-to-surface and surface-to-bulk contributions, giving us new fundamental insights into the scattering properties of the topological surface states (TSS). If the number of possible final bulk states is much larger than the number of final surface states, then the surface-to-bulk contribution is of importance, otherwise the surface-to-surface contribution dominates. Additionally, we find defect resonances that have a significant impact on the scattering properties of the TSS. They can strongly change the lifetime of the surface state to vary between tens of fs to ps at surface defect concentrations of 1 at%. We also see that the effective scattering angle shows a strong dependence on the Fermi surface warping. Our results compare fairly well with available experiments.